Short Course Basic Life Support (BLS) for Laypersons in Preventing Death Due to Cardiac Arrest - Alamsyah Alamsyah; Samsir Samsir; Sahar Sahar; Tut Handayani (SWAGATI : Journal of Community Service, 2026)
Out-of-hospital cardiac arrest (OHCA) remains a leading cause of death globally, with survival rates as low as 9–10%. Early bystander intervention through Basic Life Support (BLS)/Cardiopulmonary Resuscitation (CPR) is critical in saving lives before medical help arrives. This community service program aimed to improve the knowledge and skills of laypersons in Ko'mara Village, Pol-Sel District, Takalar Regency regarding BLS/CPR. The activity was conducted from January 12–17, 2026, involving 30 community members. Methods included a short course (lecture and simulation using CPR manikins), vital signs screening, and elderly exercise. Pre- and post-activity assessments showed a significant improvement: the proportion of participants with poor CPR ability decreased from 90% to 47%, while those with good ability increased from 10% to 53%. Knowledge also improved markedly, with 93% of participants achieving good knowledge post-intervention. These results confirm that a structured short course combining application-based learning and hands-on simulation is an effective strategy for improving BLS competency among laypersons in resource-limited communities.